The potential impact of DGEBA/amine reaction kinetics on interphase formation in glass fiber composites. (10th November 2018) - Holmes, Gale A.
Abstract: A distinctive region known as the fiber-matrix (F-M) interface/interphase (I/I) is formed between the matrix and fiber during composite manufacture. This region is assumed to be created in thermoset matrices by chemistry perturbations induced during the cure reaction. These perturbations occur at the un-sized or sized fiber surface, with the sized surface typically engineered to promote adhesion between matrix and fiber. Given the importance of this region to composite performance, potential chemistry perturbations that may arise are discussed, focusing on epoxy/amine reaction kinetics. These perturbations are linked to morphology changes that arise during fiber fracture. It is hoped that these ideas will facilitate a more complete understanding of the F-M I/I region and promote strategies for developing tougher composites.